THE EFFECT OF PBL INTEGRATED WITH PHET VIRTUAL LABORATORY AND SELF-EFFICACY ON STUDENTS’ SCIENCE PROBLEM-SOLVING SKILLS - Siregar, Indah Lastari; Hendrayana, Aan; Nulhakim, Lukman (JURNAL EDUSCIENCE, 2025)
Purpose – Mastering critical thinking and problem-solving skills is the primary demand in 21st-century education. However, the evaluation results at SMPN 2 Rangkasbitung showed that students still experienced difficulties in these aspects, which were exacerbated by using conventional learning models. For this reason, this study aims to examine the effectiveness of the Problem-Based Learning (PBL) model integrated with the PhET virtual laboratory and the role of self-efficacy in improving students' problem-solving skills on energy material.Methodology – This study used mixed methods with an explanatory sequential design. In the first stage, a quantitative approach was used to analyze the effect of PBL-PhET and self-efficacy on problem-solving ability, followed by a qualitative approach to explore the quantitative findings further. The sample consisted of 61 randomly selected grade VIII students. Data were collected through problem-solving tests, self-efficacy questionnaires, and lesson observations and analyzed using inferential statistical tests.Findings – The results showed that applying PBL integrated with PhET significantly improved students' problem-solving ability (r = 0.044). Self-efficacy also significantly influences students' problem-solving success (r < 0.001). However, the interaction between the learning model and self-efficacy did not show a significant effect (r = 0.159). The qualitative findings supported the quantitative results by showing that students with high self-efficacy were more active and confident and demonstrated more effective problem-solving strategies during problem-based learning.Significance—This research confirms the importance of integrating innovative approaches and psychological factors in science learning. Teachers and curriculum developers need to consider implementing PBL-PhET and strengthening self-efficacy as effective learning strategies relevant to the demands of the times.